PORTRAITS OF SERVICES AND INSTITUTIONAL DILEMMA OF VILLAGE MATERNITY POST (POLINDES) IN INDONESIAN TRADITIONAL AND TRANSITIONAL VILLAGES - Februati Trimurni; Yovita Sabarina Sitepu; Simson Ginting, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Village Maternity Post (Polindes) in the last decade has been present as a health facility that focuses its services on the promotion, prevention, and treatment for maternal and under five-year-old infant health. In addition, due to limited health facilities in the village, almost all existing Polindes provide general health services apart from maternal and infant health. Polindes as a health facility unit designed and implemented in accordance with the principles of community-based health development and therefore the existence and development of these facilities are adjusted to the circumstance and dynamics of the community. The circumstance and dynamics of the community are technically classified based on the village typology. The typology of the village in which the Polindes is established has a significant impact on its strategic role in health services, institutional dynamics, and development programs. This article will describe how the portrait of health services and Polindes institutions in two villages with different typologies in Langkat Regency of North Sumatra Province, Indonesia. The two villages are Kepala Sungai which represents villages with traditional typologies and Teluk Meku which represents villages with transitional typologies.